Surface egg structure and early embryonic development of the Antarctic toothfish, Dissostichus mawsoni Norman 1937 - Laura Ghigliotti; Sara Ferrando; Davide Di Blasi; CARLIG, ERICA; Lorenzo Gallus; Darren Stevens; Marino Vacchi; Steven J Parker (Polar Biology, 2018)
The Antarctic tooth sh (Dissostichus mawsoni Norman 1937) is the largest notothenioid inhabiting high-latitude Antarctic waters, where it is an important shery resource and plays a key ecological role at a high trophic level. Despite the consider- able amount of data on D. mawsoni biology and distribution developed since the shery began in 1997, crucial aspects of the life cycle, including spawning and early life history, remain undescribed. During the rst winter longline survey to the northern Ross Sea region in 2016, ripe male and female D. mawsoni were collected for the rst time, and in vitro fertilisa- tion of eggs was performed. Here, we report on the rst characterisation of D. mawsoni egg structure and initial embryonic development. The duration of the egg cleavage period was similar to that of other nototheniid species releasing pelagic eggs. The structural features of fertilised eggs, including chorion thickness and structure, support the hypothesis that eggs of D. mawsoni are pelagic. The data presented here contribute to the description of the potential habitat of the eggs of this species, and provide the rst diagnostic information to recognise the eggs of D. mawsoni.